The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mnfr.201700886
|View full text |Cite
|
Sign up to set email alerts
|

pH and Heat Resistance of the Major Celery Allergen Api g 1

Abstract: This study demonstrates that Api g 1.0101 is not intrinsically susceptible to heat treatment in vitro. However, the pH and the celery matrix strongly influence the stability of Api g 1.0101 and might be the main reasons for the observed temperature lability of this important food allergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Size Exclusion Chromatography: SEC was carried out as described previously. [12] Dau c 1.0104 (1 mg mL −1 ) was either incubated in 10 mm Na-phosphate, pH 7.0, or 10 mm Na-citrate, pH 3 for 30 min at room temperature or 95 °C and dialyzed against 10 mm Na-phosphate, pH 7. Subsequently 100 µg was loaded onto a column equilibrated with 10 mm Na-phosphate, pH 7, and 300 mm NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Size Exclusion Chromatography: SEC was carried out as described previously. [12] Dau c 1.0104 (1 mg mL −1 ) was either incubated in 10 mm Na-phosphate, pH 7.0, or 10 mm Na-citrate, pH 3 for 30 min at room temperature or 95 °C and dialyzed against 10 mm Na-phosphate, pH 7. Subsequently 100 µg was loaded onto a column equilibrated with 10 mm Na-phosphate, pH 7, and 300 mm NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…SEC was performed with all Dau c 1 proteins as described previously. [12] Fractions containing pure Dau c 1 were shock frozen and stored at 80 °C. Protein concentration was determined via the A 280 using the molar extinction coefficients derived from the ExPASy Server (Table S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance to both heat and digestion of the PR10 allergen might explain why Ballmer-Weber et al reported that over 50% of patients allergic to celery had a positive blinded oral food challenge to cooked celery, and celery spice (19). Rib-Schmidt et al determined that Api g 1 is susceptible to pH and thus the type of processing may influence the likelihood of reactions in celery allergic individuals (20). It has also been demonstrated that people who have celeriac allergy have symptoms at very low doses, with the estimated dose likely to elicit reactions in 10% of a study population (ED10) for celeriac was 1.6 mg protein, compared to the 2.8 mg of peanut protein and 8.5 mg of hazelnut protein (21).…”
Section: Resultsmentioning
confidence: 99%